(untitled) (Jahangirnagar University Journal of Biological Sciences, 2018)
An experiment was conducted at Bangladesh Institute of Nuclear Agriculture (BINA) farm, Mymensingh, Bangladesh during 2010-2011 to find out the effect of different water and organic residue levels on rice production and soil organic carbon content. Organic carbon rates from rice straw (0.5, 1.0, 1.5 and 2.0 t C ha-1 including control) were evaluated under alternate wetting and drying (AWD) and continuous flooding (CF) systems. Each treatment also received the recommended dose of chemical fertilizers excluding control. Factorial experiment was laid out in a complete randomized design with three replications. Results revealed that, maximum plant height, filled grains per tiller, 1000 grains weight, grain and straw yield were also observed in continuous flooding system in combination with 2.0 t C ha-1 in 2010 and 2011, respectively. Combined use of chemical fertilizers, 2.0 t C ha-1 fresh rice straw and continuous flooding system performed better results to reduce CO2-C gas emission, increased organic carbon and rice production with maintaining optimum soil pH level. Continuous flooding with 2.0 t C ha-1 as fresh rice straw is an effective way to reduce CO2-C emission, optimize soil pH and contribute to sustainable rice production for food security. Jahangirnagar University J. Biol. Sci. 7(1): 45-53, 2018 (June)